Child abuse in a sample of children and adolescents with externalizing disorders - Rania A Hamed; Safaa M Hammouda; Asmaa A.E. El Sehmawy (Wolters Kluwer Medknow Publications, 2020)
Objectives Many children in Egypt are being subjected to different forms of abuse. Numerous studies have documented that children exposed to child abuse are more likely to experience a set of adverse psychosocial and behavioral outcomes including low self-esteem and externalizing disorders. Patients and methods A total of 100 children and adolescents were included in the study; 50 of them were the case group with externalizing behavior [attention-deficit hyperactivity disorder (ADHD), conduct disorder (CD), oppositional defiant disorder] recruited from the outpatient clinic of psychiatry department, Al Zahraa University Hospital, whereas the other 50 were the control group from the outpatient clinic of Pediatric Department, Al Zahraa University Hospital. They were subjected to clinical assessment, the Wechsler Intelligence Scale, Child Trauma Questionnaire, and Coopersmith Self-Esteem Inventory. Results The most prevalent diagnoses of the externalizing disorder group were ADHD (46%), CD (26%), oppositional defiant disorder (16%), and ADHD with CD (12%). Comparison between the case group (externalizing disorders) and the control group regarding different types of abuse showed that there was statistically significant difference regarding emotional abuse, severe physical abuse, sexual abuse, and physical neglect. Comparison between different types of abuse in different diagnoses showed that both ADHD and CD are significantly associated with severe physical abuse and sexual abuse. The relation between self-esteem and different types of abuse showed that all types of abuse are significantly associated with low self-esteem. Conclusion The results highlight the need for strategies aiming at reducing child abuse and improving parenting style.